THE ROLE OF INNOVATIVE EDUCATIONAL TECHNOLOGIES IN FORMING ECOLOGICAL CULTURE IN STUDENTS - Khusnetdinov Ulugbek Imametdinovich (Bright Mind Publishing, 2025)
This article analyzes, from a theoretical and academic perspective, the didactic potential of innovative educational technologies in shaping environmental culture among student youth. It is assumed that activating students' learning activity through digital education, interactive methods, and information and communication technologies is a crucial factor in developing ecological thinking, awareness, and forming environmental competence.
Keywords: Environmental culture, innovative educational technologies, student youth, ecological thinking, digital pedagogy, information and communication tools, environmental competence, interactive methods, sustainable development ideas, ecological awareness.